Attitudes about sex education for children and adolescents parents in a private polyclinic in Lima - Marchena Cárdenas, Carlos Efraín (2015)
The method used in this research is descriptive, quantitative and no experimental. For its realization, the development of a Likert Measuring Scale was required. A first version of the instrument called “Scale of attitudes toward sexual education of children (ACSEX)” was applied to a pilot group, it was presented to the experts judgment and the corresponding statistical analysis was performed; the statistical correlation of items allowed to develop the final version of the instrument with three constructs. A test with a valid construct was obtained and it was individually applied to 243 parents. The majority of the sample examined has a higher education degree and a middle class socioeconomic status. Also, the sample consisted mainly of nuclear families with a small number of members. Among the findings it was found that, both fathers and mothers, have similar attitudes towards sex education of their daughters and sons, openness to sexual education of their children, parental consent to the use of contraception methods by their daughters and sons, and tolerance to the beginning of their sexual activity. However, there are notable differences in the analysis of certain variables. It was found that parents with higher level of education who live in Lima and those who have received information related to sexual education show more tolerance towards the use of contraceptive methods, than those from other cities with lower levels of instruction and less management of information related to sexual education. We found that both fathers and mothers hold similar attitudes towards sex education of children, on the opening for the sexual education of children, parents’ acquiescence of contraceptive use by children and tolerance in the beginning of the sexual activity. However, the differences are noticeable when certain variables are analyzed. Thus, parents with more education, those from Lima and those with further training in sex education are more permissive, tolerant of contraceptive use than those from other cities, with less education and training.